UWB slot-loaded Antipodal Vivaldi Antenna for through-the-wall radar imaging (TWRI) applications - Ahmed Sajjad; Joret Ariffuddin; Katiran Norshidah; Abbasi Muhammad Inam; Aminuddin Nuramin Fitri (Serbian Journal of Electrical Engineering)
The study presents an Ultra-Wideband Slot-loaded Antipodal Vivaldi Antenna (SL-AVA) designed for through-the-wall radar imaging (TWRI) applications. The antenna incorporates rectangular slots of varying lengths and widths, effectively extending its electrical length and suppressing surface waves. These variable-length slots play a crucial role in enhancing overall performance by improving bandwidth, impedance matching, and radiation characteristics. Fabricated on a Rogers 5880 substrate with dimensions of 60.50 × 66.10 mm², the SL-AVA operates efficiently across a wide frequency range of 3 GHz to 10 GHz. It achieves a peak gain of 11 dBi. Experimental fabrication and testing validate the SL-AVA antenna’s characteristics, including compact size, high gain, ultra-wide bandwidth, and directional radiation, making it an excellent choice for TWRI applications.